Analisis Implementasi Peranan Sistem Reservasi Pada Bisnis Di Sektor Industri - Ranti Kivania; Amelia Novianti; Ricky Firmansyah (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
Entering an era of increasingly advanced technological development or industrial sectors called the 4.0 industrial revolution with the help of advanced technology, the technological revolution greatly changed the accommodations around the world, the application or system technology revolution of the world. Business can be done online or offline where the system is made for reservations on other days. The system is called reservation system, the benefits of a reservation system to make it easier for people to enjoy various accommodations in business quickly and there will be no delay if they want to enjoy facilities or places. As opposed to a business, reservation systems in various businesses have the advantages and effectiveness of running a business. Meanwhile, reservation is a facility or place reservation system. The reservation itself is a request by the guest to obtain the desired facilities or places after going through the reservation system in the hope that there will be no constraints when on a reserved day, the method of collecting data through various scientific works by processing the data to become a research material literature study.